Expression of insulin-like growth factor 1 receptor (IGF-1R) predicts poor responses to epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors in non-small cell lung cancer patients harboring activating EGFR mutations. Issue 3 (March 2015) - Yeo, Chang Dong; Park, Ki Hoon; Park, Chan Kwon; Lee, Sang Haak; Kim, Seung Joon; Yoon, Hyung Kyu; Lee, Youn Soo; Lee, Eun Jung; Lee, Kyo Young; Kim, Tae-Jung
Highlights We determined the relationship IGF-1R expression and the response to EGFR-TKIs in patients harboring activating EGFR mutations. Expression of IGF-1R was independently associated with shorter PFS in a response to EGFR-TKIs. Patients with DM highly expressed IGF-1R in tumor tissues. DM was associated with a poor response to first-line TKI therapy.